1937
DOI: 10.1021/ac50108a022
|View full text |Cite
|
Sign up to set email alerts
|

Microanalysis of Nitrogen in Certain Pyrimidines by the Dumas Method

Abstract: micro-Dumas method of Pregl (S) has an enviable reputation for producing accurate results on a variety of substances. Properly handled, it was considered an accurate method for any organic nitrogen-containing compound.This method was used in this laboratory on a wide range of compounds without any known discrepancy until a certain series of pyrimidines of known purity failed to give the required amount of nitrogen. The nitrogen values obtained were from 0.4 to 2.0 per cent below theory and were reproducible un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1938
1938
1966
1966

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A REVIEW of procedures for the Dumas microdetermination of nitrogen in refractory substances has shown the need for a simple method applicable to both tractable and refractory compounds. Some of the existing methods which claim excellent results (9,18) are not of general applicability-for instance, the potassium chlorate method of Spies and Harris (18) and the copper acetate method of Hayman and Adler (9) were applied to pteridines without success (1). Brancone and Fulmor (1) were able to analyze pteridines merely by raising the temperature of the movable burner to 900"C.; oxidation aids were omitted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A REVIEW of procedures for the Dumas microdetermination of nitrogen in refractory substances has shown the need for a simple method applicable to both tractable and refractory compounds. Some of the existing methods which claim excellent results (9,18) are not of general applicability-for instance, the potassium chlorate method of Spies and Harris (18) and the copper acetate method of Hayman and Adler (9) were applied to pteridines without success (1). Brancone and Fulmor (1) were able to analyze pteridines merely by raising the temperature of the movable burner to 900"C.; oxidation aids were omitted.…”
mentioning
confidence: 99%
“…tional Dumas method: A carefully controlled combustion with painstaking observation of bubble speed is required, if accuracy and reproducibility are to be achieved ( 14). If the Dumas method is adapted to the analysis of refractory compounds by adding oxidation aids (7,9,18), the changes involved may cause inconsistent results, as some investigators have reported (1,8,10,17). Without certain modifications, however, refractory compounds, such as certain pyrimidines, purines, and pteridines, give extremely erratic results (1, 8-10, 12, 13, 17, 18).…”
mentioning
confidence: 99%